2014
DOI: 10.1042/bst20140181
|View full text |Cite
|
Sign up to set email alerts
|

C1 domain-targeted isophthalates as protein kinase C modulators: structure-based design, structure–activity relationships and biological activities

Abstract: Protein kinase C (PKC) is a serine/threonine kinase belonging to the AGC family. PKC isoenzymes are activated by phospholipid-derived second messengers, transmit their signal by phosphorylating specific substrates and play a pivotal role in the regulation of various cell functions, including metabolism, growth, differentiation and apoptosis. Therefore they represent an interesting molecular target for the treatment of several diseases, such as cancer and Alzheimer's disease. Adopting a structure-based approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…PKC is a phospholipid-dependent serine/ threonine kinase family. Tis family comprises 13 isoenzymes that can be activated by extracellular signals [40]. Te active state of PKC is p-PKC, which is a phosphorylated state [41,42] and is implicated in various roles [43].…”
Section: Discussionmentioning
confidence: 99%
“…PKC is a phospholipid-dependent serine/ threonine kinase family. Tis family comprises 13 isoenzymes that can be activated by extracellular signals [40]. Te active state of PKC is p-PKC, which is a phosphorylated state [41,42] and is implicated in various roles [43].…”
Section: Discussionmentioning
confidence: 99%
“…Plant and animal derived natural C1 domain ligands, such as phorbol esters and bryostatins, show high affinity and biological activity but they are not optimal drug candidates as their complex chemical structures make their synthesis tedious. In our previous work, we have demonstrated that simple 5-hydroxymethyl isophthalic acid derivatives exhibit promising biological activity [ 9 , 10 , 12 , 13 ]. The lipophilicity values for the HMIs (clog P 6–7) are however higher than the Lipinski’s drug-like lipophilic property value (log P ≤5) [ 27 ] and therefore, we endeavored to synthesize a new set of compounds with reduced lipophilicity and retained/increased binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the ATP binding site in the catalytic domain is highly preserved throughout the human kinome, targeting the regulatory C1 domain greatly increases the selectivity for PKC over other kinases [ 6 , 7 ]. In addition to PKCs, there are only six other protein families, compared to more than 500 protein kinases in the human genome, containing a DAG-responsive C1 domain [ 8 10 ]. Throughout the years, several PKC activators showing higher affinity than the natural DAG were described and they represent a significant class of PKC modulators [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although various synthetic bryostatin analogues have been reported , to our knowledge, there are no reports of their effects in AD models. Among other C1 domain‐targeted compounds, the isophthalate derivatives act as partial agonists for PKC . They bind to PKC at submicromolar concentrations and activate PKC in cellular context as shown by induction of PKC‐dependent ERK1/2 phosphorylation .…”
Section: Pkc Activators As Potential Drug Candidates For Admentioning
confidence: 99%